DNA metabarcoding reveals introduced species predominate in the diet of a threatened endemic omnivore, Telfair's skink (Leiolopisma telfairii). Issue 1 (21st December 2021) - Tercel, Maximillian P. T. G.; Moorhouse‐Gann, Rosemary J.; Cuff, Jordan P.; Drake, Lorna E.; Cole, Nik C.; Goder, Martine; Mootoocurpen, Rouben; Symondson, William O. C.
Abstract: Introduced species can exert disproportionately negative effects on island ecosystems, but their potential role as food for native consumers is poorly studied. Telfair's skinks are endemic omnivores living on Round Island, Mauritius, a globally significant site of biodiversity conservation. We aimed to determine the dietary diversity and key trophic interactions of Telfair's skinks, whether introduced species are frequently consumed, and if diet composition changes seasonally between male and female skinks. We used DNA metabarcoding of skink fecal samples to identify animals (COI) and plants (ITS2) consumed by skinks. There were 389 dietary presence counts belonging to 77 dietary taxa found across the 73 Telfair's skink fecal samples. Introduced taxa were cumulatively consumed more frequently than other categories, accounting for 49.4% of all detections, compared to cryptogenic (20.6%), native (20.6%), and endemic taxa (9.5%). The most frequently consumed introduced species was the ant, Pheidole megacephala, present in 40% of samples. Blue latan palm, Latania loddigesii, was the most frequently consumed endemic species, present in 33% of samples but was only detected in the dry season, when fruits are produced. We found a strong seasonal difference in diet composition explained by the presence of certain plant species solely or primarily in one season and a marked increase in the consumption of animal prey in the dry season. Male and female skinks consumed several taxa at different frequencies. These results present a valuable perspective on the role of introduced species in the trophic network of their invaded ecosystem. Both native and introduced species provide nutritional resources for skinks, and this may have management implications in the context of species conservation and island restoration. Abstract : Telfair's skinks are keystone omnivores found on Round Island, Mauritius. Using a multimarker DNA metabarcoding approach, we identify that this endemic species frequently consumes introduced species, which comprise almost 50% of all prey detections. This provides a valuable insight into how introduced species may fit into the food web in their introduced range.